(untitled) (Global Journal of Human-Social Science, 2023)
Numerous and exhaustive studies have been carried out on the defensive system of the city of Constantinople its troops the number of those available during the different dynastic periods its successful and impregnable Theodosian walls and how they remained standing repelling foreign enemies attacks during more than ten centuries ignoring the civil and internecine wars that the Empire suffered during this prolonged period The Imperial Byzantine capital suffered more than thirty attacks being the most notable one carried out by the Crusaders in 1204 which as is well known ended with the devastating Crusader looting of one of the richest cities in the world